Remote Sensing Applications in Archaeology, Geography, and the Earth Sciences (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Archaeology, geography, and the Earth sciences are an integrated field devoted to researching nature, the environment, humanity, and the social sciences. Remote sensing systems have been widely applied for data acquisition at various spatial scales. Innovations in image and signal processing, IoT, big data, and deep learning models induce new potentials in the reconstruction and exploration of ancient people’s material culture and lives. This Special Issue focuses on applying remote sensing techniques coupled with a data mining method to analyze and discuss humanity-, geography-, and environment-related contexts. The formal integration of archaeology and geography has been conducted over the past twenty or thirty years. In spite of this, continuous innovations, whether in imaging spectroscopy and multimodal imaging or in imaging computing using deep learning models, still motivate scholars to address related issues. The aim of this Special Issue is to compile the latest achievements in the field and to open up a forum where scholars can contribute their unique findings.